Cornfood bar (Zea mays l) and Goroho banana (M. Accincanafe) as alternative foods interlude people with type 2 diabetes mellitus - Indra Domili; M Anas Anasiru (AcTion: Aceh Nutrition Journal, 2024)
The World Health Organization (WHO) reported an increase in type 2 diabetes cases in Indonesia, from 8,4% in 2000 to 21,3 in 2030. Functional food innovation to prevent diabetes in the form of corn and Goroho banana-based food bars needs to be performed. This study aimed to determine preference and nutritional value in a preliminary study of food innovation. This research method used a one-variable completely randomized experimental design (CRD), three treatments; ratio of corn and goroho banana; F-1 (90:10), F-2 (80:20), and F-3 (70:30). The preference test was conducted in the organoleptic laboratory of the Nutrition Department of Gorontalo Health Polytechnic using 30 semi-trained panelists to obtain the most preferred formula based on the ranking test presented in averages and analyzed using the Friedman test followed by the Wilcoxon post-hoc test. The nutritional value of the food bars was tested at the Gadjah Mada University Food Laboratory from May to June 2020. Results of preference level for corn-based food bars (zea mays l) and goroho banana-based food bars (M. Accuminafe) sequentially F-1 (90:10) with a mean of 3,40, nutritional value  of 4,76% fat, 7,28% protein, 66,21% carbohydrates, and 1,28% crude fiber. In conclusion, F-1 was selected as a food source for people with diabetes mellitus.